Long Term Follow Up of Hemangioma on Bilateral Cleft Lip - Atmodiwirjo, Parintosa; Lestari, Puri Ambar; Kesuma, Ayu Diah (Jurnal Plastik Rekonstruksi, 2013)
Background: Hemangioma is a common tumor of infancy that exhibits rapid postnatal growth and slow regression during childhood. Cleft lip is a common anomaly found in Indonesia. These entities are twice in common in the Asian population. However, simultaneous occurance of these two abnormalities is rare to be found. Patient and Method: A case of bilateral cleft lip complicated with hemangioma on the left side of lip and the surrounding skin through the mucosa, and the prolabium, which had been performed cheiloplasty procedure at age 9 months old. Cheiloplasty design was made through the hemangioma area with a careful hemostasis to avoid massive bleeding. Result: Hemangioma was partially left behind at the cheiloplasty procedure. There was no bleeding during and after the surgery. Two years following the surgery, there was a fine scar with good shape of the lip and no further growth of the hemangioma. Summary: Hemangioma and cleft lip are very rare to be found in the same location. Because of the involution potential of hemangioma, timing of surgery is very important. Considering the psychosocial aspect, the surgery was performed at the age of 9 months. Two years after surgery, we didn’t find any growth of hemangioma or deformity of the bone and lip. The scar growth is in good esthetic result, no difference with left lip child without hemangioma.